Effectiveness of traditional herbal Kampo medicine Goreisan on chronic subdural hematoma recurrence: a meta-analysis - Yang, Zhenyu; Zeng, Yuecheng; Hu, Jinyang; Huang, Xin; Zhang, Haiquan; Liu, Yang (Frontiers in Pharmacology, 2024)
Objectives: Our objective was to compare the effectiveness of Traditional Chinese herbal Kampo medicine Goreisan in improving recurrence in patients with chronic subdural hematoma (CSDH). Methods: Eligible randomized controlled trials (RCTs), prospective trials, and retrospective cohort studies were systematically identified through searches of PubMed, Cochrane Library, and CNKI from inception to March 2024. Following the application of predetermined inclusion and exclusion criteria to screen the available studies, main outcome measures were rigorously extracted. RevMan v5.4 software was utilized to evaluate the overall recurrence rate, employing a random-effects model to calculate pooled odds ratios (ORs) with the Mantel-Haenszel estimation method. Inter-study heterogeneity was assessed using the Cochran Q (Chi-square) test and I2 statistics. Funnel plots were used to evaluate publication bias. Results: Among the 48 articles initially screened for citation, 8 were ultimately selected for inclusion in the study. The results of our network meta-analysis (NMA) indicate that patients with newly diagnosed Chronic subdural hematoma experienced a significantly reduced recurrence rate when treated with Goreisan compared to standard neurosurgical treatment (OR: 0.72; 95% CI 0.61–0.86; p = 0.00003). There was no statistically significant difference in the incidence rates of complications, including general fatigue, allergic reactions, hepatic dysfunction, and interstitial pneumonia (OR: 7.21; 95% CI 0.37–141.29; p = 0.19). Conclusion: Traditional medicine Goreisan was effective in reducing CDSH recurrence rates. For clinical treatment, it provides a high level of evidence-based medicine. It is also necessary to conduct multicenter randomized controlled trials with dose adjustments to determine whether Goreisan interventions improve neurological function or prognosis.